2014
DOI: 10.1021/ic5003836
|View full text |Cite
|
Sign up to set email alerts
|

Improving SERS Activity of Inositol Hexaphosphate Capped Silver Nanoparticles: Fe3+ as a Switcher

Abstract: Inositol hexaphosphate (IP6) capped silver nanoparticles (IP6@AgNPs) were fabricated as surface-enhanced Raman scattering (SERS) active substrates. SERS activity of IP6@AgNPs could be further improved via adding due amounts of Fe(3+) to form Fe(3+)-IP6@AgNPs. The mechanism of Fe(3+)-induced SERS improvement of IP6@AgNPs can be attributed to the strong interaction of IP6 and Fe(3+), which leads to controllable adjustment of the gap among neighboring nanoparticles to produce "hot spots". The above mechanism was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…However, the LOD of R6G could reach 5 × 10 −8 M when the R6G was mixed with OTR 202 colloids. The Raman EF was used to measure the enhancement effect, which was calculated as follows [35]:EF=ISERSCRamanIRamanCSERS where ISERS is the integrated intensity of R6G molecules adsorbed on the colloids surface; IRaman is the integrated intensity of the same Raman band obtained without the OTR 202 colloids; CSERS represents the concentration of R6G adsorbed on OTR 202 colloids; and CRaman represents the concentration of R6G that can be detected by ordinary RS.…”
Section: Resultsmentioning
confidence: 99%
“…However, the LOD of R6G could reach 5 × 10 −8 M when the R6G was mixed with OTR 202 colloids. The Raman EF was used to measure the enhancement effect, which was calculated as follows [35]:EF=ISERSCRamanIRamanCSERS where ISERS is the integrated intensity of R6G molecules adsorbed on the colloids surface; IRaman is the integrated intensity of the same Raman band obtained without the OTR 202 colloids; CSERS represents the concentration of R6G adsorbed on OTR 202 colloids; and CRaman represents the concentration of R6G that can be detected by ordinary RS.…”
Section: Resultsmentioning
confidence: 99%
“…However, the deltamethrin at 999 cm −1 with a concentration of 2 × 10 −7 M is still obvious using 75 nm AuNPs as SERS substrates. In this work, the enhancement factor (EF) of deltamethrin at 999 cm −1 was calculated from Equation (1) [ 41 , 42 , 43 ]: where is the integrated intensity of deltamethrin molecules adsorbed on the substrate surface. is the integrated intensity of the same Raman band obtained without the AuNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this opinion, one kind of reagent that not only could aggregate metal nanoparticles to produce plenty of hot spots for elevating SERS effect but also could interact with analyte molecules for adsorbing more molecules on the surface of SERS substrate is desirable for SERS detection. In our previous work, the result that adding Fe 3+ into inositol hexaphosphate (IP 6 ) micelle capped silver nanoparticles (IP 6 @AgNPs) produce plenty of hot spots for greatly improving sensitivity of SERS has been investigated . Coincidentally, Chen and Liu reported that metal ions (Fe 3+ , Zn 2+ , Ca 2+ , etc.)…”
Section: Introductionmentioning
confidence: 99%